Decoder for quadrature Interference Signals - Kosyak, I. V. (Інститут проблем реєстрації інформації НАН України, 2013)
The analysis and research of interference signals of the interferometric system for measuring ultra-small linear movements has been accomplished. The features of devices performing reverse counting the numbers of interference fringes are considered. The realization of the device reversely counting the in-crement intervals for the signal’s phase has been suggested. Fig.: 7. Refs: 13 titles.